Definition and performance simulations of a novel solar-driven hybrid absorption-thermochemical refrigeration system. (1st November 2018) - Fitó, Jaume; Coronas, Alberto; Mauran, Sylvain; Mazet, Nathalie; Stitou, Driss
Graphical abstract: Highlights: Novel absorption–thermochemical hybrid system for refrigeration and energy storage. Thermodynamic analysis and parametric study with some ammonia-based working pairs. Ammonia as refrigerant, LiNO3 as sorbent and BaCl2 as reactive salt are promising. Coefficient of Satisfaction of Demand (CSD) proposed to quantify storage function. The hybrid system has better CSD than an absorption system alone and similar COP. Abstract: This paper proposes a novel hybrid refrigeration system with energy storage, driven by low-grade solar heat and consisting of a single-stage absorption cycle coupled with a thermochemical process by sharing the same condenser, evaporator and refrigerant fluid. A first screening of ammonia-based working pairs for evaporation temperatures of −10 °C, condensation temperatures of 30 °C and heat source temperatures of 80 °C reveals LiNO3 as suitable sorbent salt for the absorption subsystem, and BaCl2, PbBr2, SrCl2, LiCl, NH4 Br and SnCl2 as candidate reactive salts in the thermochemical subsystem. The subsequent parametric study indicates that the absorption subsystem with NH3 /LiNO3 reaches close-to-maximum COP at the indicated conditions, and the thermochemical subsystem delivers its highest COP with the NH3 /BaCl2 pair. Then, the power-storage and performance-storage relationships of the thermochemical subsystem are analyzed for the NH3 /BaCl2 pair with respect to variations in operating conditions and several implementation parameters of the reactive composite. Finally, the performance of the hybrid system with the (NH3 /LiNO3  + NH3 /BaCl2 ) pair combination is compared to its subsystems against a variable demand profile calculated from climatic data of July in Barcelona, Spain. A novel indicator is defined to assess demand coverage: the Coefficient of Satisfaction of Demand (CSD). Depending on solar collector field area and amount of refrigerant storable by the thermochemical subsystem, the hybrid system reaches up to 24% higher CSD than the reference system (a solar single-stage absorption refrigerator with no storage), and at least 14% higher COP than the thermochemical process.